Factors Associated with Placenta Praevia in Primigravidas and Its Pregnancy Outcome. (11th November 2014) - Nur Azurah, Abdul Ghani; Wan Zainol, Zakaria; Lim, Pei Shan; Shafiee, Mohd Nasir; Kampan, Nirmala; Mohsin, Wan Syahirah; Mokhtar, Norfilza Mohd; Muhammad Yassin, Muhammad Abdul Jamil
Abstract : Aim. To examine the factors associated with placenta praevia in primigravidas and also compare the pregnancy outcomes between primigravidas and nonprimigravidas. Method. A retrospective cohort study was conducted in women who underwent caesarean section for major placenta praevia in a tertiary university hospital from January 2007 till December 2013. Medical records were reviewed. Result. Among 243 with major placenta praevia, 56 (23.0%) were primigravidas and 187 (77.0%) were nonprimigravidas. Factors associated with placenta praevia in the primigravidas were history of assisted conception (P = 0.02 ) and history of endometriosis (P = 0.01 ). For maternal outcomes, the nonprimigravidas required earlier delivery than primigravidas (35.76 ± 2.54 weeks versus 36.52 ± 1.95 weeks, P = 0.03 ) and had greater blood loss (P = 0.04 ). A vast majority of the primigravidas had either posterior type II or type III placenta praevia. As for neonatal outcomes, the Apgar score at 1 minute was significantly lower for the nonprimigravidas (7.89 ± 1.72 versus 8.39 ± 1.288.39 ± 1.28, P = 0.02 ). Conclusion. This study highlighted that endometriosis and assisted conception were highly associated with placenta praevia in primigravida. Understanding the pregnancy outcomes of women with placenta praevia can assist clinicians in identifying patients who are at higher risk of mortality and morbidity. Identifying potential risk factors in primigravida may assist in counseling and management of such patients.